Research on urban resilience assessment and driving forces based on Production-Living-Ecological Spaces: A case study of the Three Gorges Reservoir Area in China - Honglin Liu; Junjie Zhu; Ziming He (PLoS ONE, 2025)
This study aims to develop a resilience evaluation approach based on production-living-ecological spaces and identify the key drivers of urban resilience in less-developed areas, taking the Three Gorges Reservoir Area in China as a case study. Understanding how to increase urban resilience and how to coordinate the three types of space in urban areas is critical for the healthy and stable development of cities. In this work, we develop an integrated assessment methodology for resilience in three dimensions: production space, living space, and ecological space. The geographical agglomeration impact is studied using the spatial approach, such as the Jenks natural breakpoint method and spatial autocorrelation analysis. Geographic Detectors are used to identify the drivers and to provide tailored optimization solutions. It was discovered that: (1) from 2010 to 2020, the comprehensive resilience of counties in the Three Gorges Reservoir Area of China continues to increase, as does the sub-spatial resilience; (2) both the resilience of counties and the sub-spatial resilience exhibit “unbalanced” characteristics, and the spatial distribution exhibits “randomization”. There appears to be no evident clustering influence; (3) each county’s production space has a high level of resilience, which is the component that has the greatest influence on the county’s total resilience and the living space is next, followed by the ecological space; (4) the vast majority of interactions between the driving factors are two-factor enhancement, with just a small percentage being non-linear enhancement. The study’s findings can provide theoretical guidance and technical help for the study of urban resilience in less-developed locations. Furthermore, the findings are extremely important for the development of resilient cities.